HAMBATAN-HAMBATAN YANG DIHADAPI MAHASISWA PL PRODI PENDIDIKAN SEJARAH STKIP PGRI SUMBAR DALAM MEMBUAT PERANGKAT PEMBELAJARAN PADA SEMESTER GENAP T.A 2013/2014 - Yulani, Andrisa Okta (Pendidikan Sejarah, 2014)
The background of the study was to determine the barriesrs raced by students of the practice field department of history education in creating a learning device in the from of KKM, Syllabus and RPP. this type of research is a qualitative research respondents in this study is the history of the education department of the practice field students STKIP PGRI Sumatera Barat and teacher education study program tutors students practice field history STKIP PGRI Sumatera Barat. The research location is junior high school Muhammadiyah 6 Padang, senior high school 4 Pariaman, senior high school 1 Pacung Soal districts Pesisir Selatan and senior high school 1 Tigo Villages districts Pasaman. Field of research data collection was conduted interviews students of the practice field dapartement of history STKIP PGRI Sumatera Barat and teacher education. From the research it was found that the abstacles in making the learning device in the from of the KKM, Sylabus and RPP (1) barriers in the from of making KKM determine cognitive, psychomotor and affective as well as the determination and calculation of the score assigned. (2) barriers in the from of making the syllabus specify the character to be owned learners, determining learning activities in the from of TM, PT, KMTT the allocation of time for the necessary learning materials in teaching and learning in every basic competency. (3) barriers in making lesson plans from the core activities of learning plan drawn up in exploration, elaboration and confirmation, as well as learning met hods in order to determine the achievement of learning goals. From study it can be concluded that the students of the history department of education STKIP PGRI Sumatera Barat still faces obstacles in making the learning. Therefore, attention and guidance from faculity of education department of history and civil school teacher training is needed in the process of creating a learning device.